(3TQM WQaI GdWdGH dfXe bSei GdNWGHs - (3eMeO Hf eMeO Hf MSf GdCgOds; (3CHh HcQ Hf CHj GdbGSe GdGgOds
(3ChdgG (B:s
(3bGd SjOfG GdSjO eMeO Hf eMeO Hf MSf GdCgOd QMeg dGdg , Bejf , bhd GdfGXe QMeg Gddg s
(3BNQgG (B:s
(3bGd GdeDda faY Gddg Hg (B: (3Je GdTQM GddWja GdePchQ Ydi GdhLg GdeSWhQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HPjdgG JQLeI ddTGQMs
(3cJHJ CHjGJ GdefXheI HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdTjN eMeO YHO GdLdjd GdZRi GdNGUg HRHjO s
Keywords: (3Gdabg GdESdGejs